{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

note12

# note12 - Math021 week 12 Partial Fractions Example 12.1...

This preview shows pages 1–4. Sign up to view the full content.

Math021, week 12 Partial Fractions Example 12.1 Evaluate Z dx x 2 - 1 . solution: Since 1 x 2 - 1 = 1 ( x - 1)( x +1) , we will try finding two numbers A and B such that 1 ( x - 1)( x + 1) = A x - 1 + B x + 1 if possible. If such numbers A and B are there, they satisfy 1 ( x - 1)( x + 1) = ( A + B ) x + ( A - B ) ( x - 1)( x + 1) for all x . That is, we need A + B = 0 and A - B = 1. The choice A = 1 / 2 and B = - 1 / 2 does the job. Thus, 1 ( x - 1)( x + 1) = 1 2 ( 1 x - 1 - 1 x + 1 ) . Finally, R dx x 2 - 1 = 1 2 R ( 1 x - 1 - 1 x +1 ) dx = 1 2 (ln( x - 1) - ln( x + 1)) + C = 1 2 ln x - 1 x +1 + C. Remark 12.2 In the previous example, we split a fraction into a sum of several simpler fractions. Such technique is called the technique of partial fractions. Example 12.3 Evaluate Z sec xdx. 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
solution: Let u = sin x so that du = cos xdx . Then, R sec xdx = R cos xdx 1 - sin 2 x = R du 1 - u 2 = 1 2 R ( 1 1 - u + 1 1+ u ) du = 1 2 ( - ln(1 - u ) + ln(1 + u )) + C = 1 2 ln 1+sin x 1 - sin x + C Example 12.4 Evaluate Z x 3 dx x 2 - 1 solution: Note that x 3 = x ( x 2 - 1) + x, we have x 3 x 2 - 1 = x ( x 2 - 1) x 2 - 1 + x x 2 - 1 = x + 1 2 x - 1+ x +1 ( x - 1)( x +1) = x + 1 2 ( 1 x - 1 + 1 x +1 ) . Hence, R x 3 dx x 2 - 1 = R [ x + 1 2 ( 1 x - 1 + 1 x +1 )] dx = 1 2 ( x 2 + ln( x - 1) + ln( x + 1)) + C = 1 2 ( x 2 + ln( x 2 - 1)) + C. Example 12.5 Evaluate Z x + 1 x ( x - 1) 3 dx solution: We will try finding three numbers A and B such that x + 1 x ( x - 1) 3 = A x + B ( x - 1) 3 if possible. If such numbers A and B are there, they satisfy x + 1 x ( x - 1) 3 = A ( x - 1) 3 + Bx x ( x - 1) 3 for all x . That is, we need A ( x - 1) 3 + Bx = x + 1 for all x . Putting x = 1 yields B = 2 and putting x = 0 yields A = - 1. But it is obvious that - ( x - 1) 3 + x 6 = x + 1!! We conclude that such numbers A and B are not 2
there. To rectify the situation, we will see if there are numbers A , B , C , D such that x + 1 x ( x - 1) 3 = A x + B ( x - 1) 3 + C ( x - 1) 2 + D x - 1 .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 9

note12 - Math021 week 12 Partial Fractions Example 12.1...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online